Medicare short-stay hospital services by diagnosis-related groups - Latta, Viola B. (CENTERS for MEDICARE & MEDICAID SERVICES, 1991)
The 1983 amendments to the Social Security Act (Public Law 98-21) provided for a prospective payment system (PPS), effective October 1, 1983, for most short-stay hospitals certified to provide inpatient services to Medicare beneficiaries. A brief description of the assignment process for diagnosis-related groups (DRGs) is presented, because assigning a DRG code to a short-stay hospital discharge record is tantamount to the Medicare prospective payment to the hospital, subject to certain statutory adjustments. Shifts in the distribution of the discharges and average length of stay among the DRGs since 1983 reflect the adaptation of hospitals to the incentives embedded in PPS and the ongoing refinements in the methods of assigning DRGs to discharges from short-stay hospitals. Interpretation of the shifts is based on a consideration of the significant refinements in the medical coding system, the technological and scientific advances in the practice of medicine, the effect of shifting patient treatment to alternative sites, policy or legislative changes affecting Medicare coverage, and the annual recalibration of the DRG weights.